2023
DOI: 10.1177/08912432231171171
|View full text |Cite
|
Sign up to set email alerts
|

Building the Settler Colonial Order: Police (In)Actions in Response to Violence Against Indigenous Women in “Canada”

Abstract: In this article we focus on missing and murdered Indigenous women, girls, and 2SLGBTQQIA people in “Canada.” We theorize narratives that police employ to respond to this violence. Using a broad data sample of testimonies across “Canada,” this article contributes to understanding how police (in)actions make sense of, justify, and dismiss violence against Indigenous women, girls, and 2SLGBTQQIA people. We draw from 48 in-depth semi-structured interviews with Indigenous peoples in Toronto and other “Canadian” cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Several reports and studies revealed discrimination against Indigenous community members by the police [ 66 ]. The relationship between Indigenous communities and the police may also be influenced by historical colonial practices, in which the police was a major law enforcement instrument; these practices exposed Indigenous communities to systemic social inequities and inter-generational trauma, resulting in disproportionate and frequent encounters with police as law violators or victims [ 66 68 ]. Similar experiences with the police, characterized by loss of confidence and dissatisfaction with police performance and fairness, have also been reported in Black Canadian communities [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports and studies revealed discrimination against Indigenous community members by the police [ 66 ]. The relationship between Indigenous communities and the police may also be influenced by historical colonial practices, in which the police was a major law enforcement instrument; these practices exposed Indigenous communities to systemic social inequities and inter-generational trauma, resulting in disproportionate and frequent encounters with police as law violators or victims [ 66 68 ]. Similar experiences with the police, characterized by loss of confidence and dissatisfaction with police performance and fairness, have also been reported in Black Canadian communities [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soon after, a class action was started by Margorie Hudson, a long-serving Indigenous female member, on behalf of any racialized employees subjected to racial discrimination and harassment based on race that stunted careers and advancement (McKinley, 2023). Complaints handled by an independent civilian review commission and forwarded to the commissioner included accusations of racial profiling and sexual preying on young Indigenous girls by on-duty RCMP/GRC members (Flores and Román Alfaro, 2023).…”
Section: Buffing a Tarnished Brandmentioning
confidence: 99%